TINGKAT KEPUASAN KONSUMEN DI TOKO BUNGA CINTA FLORIST KE-LURAHAN KAKASKASEN II KECAMATAN TOMOHON UTARA KOTA TOMOHON (Level of Customer Satisfaction in â€œCinta Floristâ€ Kakaskasen Two North Tomohon District Tomohon City) - Tumbelaka, Stevanny; Pakasi, Caroline B. D.; Sendow, Martha M. (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2021)
This study aimed to determine the level of consumer satisfaction to the flower products in the flower shop "Cinta Florist", Kakaskasen Dua Subdistrict, North Tomohon District, Tomohon City. This research was conducted from December 2019 to January 2020. This research used primary data obtained directly from consumers using questionnaires, and secondary data obtained from literature studies and relevant sources. The results showed that the level of satisfaction of the flower consumers at the Cinta Florist Kakaskasen Dua in Tomohon City falled into the criteria of "satisfied", with a consumer satisfaction index of 71.7%. In general, consumers were satisfied with the flower prices given by Cinta Florist because it was in accordance with high-quality, fresh and durable flower products.